Rock engineering - Palmström, Arild (Thomas Telford, 2010)
With a focus on risk and uncertainty, 'Rock engineering' explains the geological principles and concepts required for successful geotechnical design and engineering of underground excavations.
Keywords: Rock mechanics.; Excavation.; Engineering geology.; elektronické knihy; electronic books